In-Between Discourse and Genre: Doctor-Patient Interaction in Online Communication. - Zummo Marianna Lya (Romanian Journal of English Studies, 2012)
This paper presents the results of a corpus-based study which investigates the genre of medical eexchanges between doctors and medical website users. Three conversational routines (greetings, politeness, formal and informal linguistic features) are analyzed. The framework of the study is what some researchers refer to as net linguistics (Posteguillo 2003), consisting of the linguistic study of Computer Mediated Communication (CMC). The findings indicate that health posts are a relatively informal type of d/p interaction which is largely influenced by e-mails and chat conventions.